Ideational semiosis: a tri-stratal perspective on grammatical metaphor - Martin, James R (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
This paper addresses the challenge of analysing texts for ideational grammatical metaphor. It undertakes this task from the perspective of recent work on fi eld (Doran & Martin in press) and discourse semantics (Hao 2020a). In doing so it highlights the benefi ts of adopting a tri-stratal perspective on experiential and logical grammatical metaphor (Hao 2020b) – bringing all three of the most relevant strata (i.e. fi eld, discourse semantics and lexicogrammar) into the picture.